Does ischemic pre-conditioning during the recovery period between two successive matches preserve physical performance in badminton doubles players? - Olivier Girard; Franck Brocherie; Mohammed Ihsan (International Journal of Racket Sports Science, 2020)
Changes in physical performance were assessed in response to two successive doubles badminton matches with implementation of ischemic pre-conditioning (IPC) or sham treatment during recovery period between matches. Eight French national team badminton players (4 males, 4 females) performed two successive doubles matches (2 × 45 min), with 60 min of recovery in-between, during which they received three 5-min cycles of either an IPC (220 mmHg) or a sham (SHAM) (50 mmHg) intervention. A series of physical tests was performed immediately following the first (Post 1) and second (Post 2) match. Jump height (squat and countermovement jumps), leg power (multi-rebound jumps) and sprint time (L-test) remained unchanged from Post 1 to Post 2 (all P>0.193), and did not differ between conditions (all P>0.173). During a badminton-specific repeated-agility test, neither performance-related variables (i.e., best time, total time and sprint decrement score) nor vastus lateralis muscle tissue saturation index displayed a main effect for condition (all P>0.116), time (all P>0.091) or time × condition interaction (all P>0.730). Implementing IPC during the recovery period between successive doubles badminton demonstrated no beneficial effect on physical performance and muscle oxygenation trends.